2015
DOI: 10.2147/chc.s71852
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cancer cell mechanical properties after fluid shear stress exposure: a micropipette aspiration study

Abstract: Over 90% of cancer deaths result not from primary tumor development, but from metastatic tumors that arise after cancer cells circulate to distal sites via the circulatory system. While it is known that metastasis is an inefficient process, the effect of hemodynamic parameters such as fluid shear stress (FSS) on the viability and efficacy of metastasis is not well understood. Recent work has shown that select cancer cells may be able to survive and possibly even adapt to FSS in vitro. The current research seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 33 publications
1
38
1
Order By: Relevance
“…Lee et al (2017) showed that mechanical forces exerted by the fluid flow regulate cell behavior, being crucial for the metastasis process . Chivukula et al (2015) also demonstrated that cancer prostate cells may be able to adapt to the fluid shear stress (FSS). Micropipette aspiration was used to measure the Young's modulus of prostate epithelial and prostate cancer cells.…”
Section: Invasionmentioning
confidence: 99%
“…Lee et al (2017) showed that mechanical forces exerted by the fluid flow regulate cell behavior, being crucial for the metastasis process . Chivukula et al (2015) also demonstrated that cancer prostate cells may be able to adapt to the fluid shear stress (FSS). Micropipette aspiration was used to measure the Young's modulus of prostate epithelial and prostate cancer cells.…”
Section: Invasionmentioning
confidence: 99%
“…It has already been discussed that cancer cells have higher viability rates after fluid shear stress exposure. It has also been shown that cancer cells exhibit different mechanical properties compared to non-cancerous cells before and after exposure to shear stress (Chivukula et al, 2015). Before exposure to shear stress, the elastic modulus of epithelial cells in this study was about 2.4 times that of the cancer cells.…”
Section: Background In Cancer Cell Mechanicsmentioning
confidence: 46%
“…The occlusion of blood flow in the capillary increases the pressure gradient across the cell, potentially leading to membrane failure. This hypothesis seems unlikely; micropipette and microfluidic experiments can apply high pressure gradients across cancer cells without causing membrane failure (Chivukula et al, 2015). The highly parallel nature of capillary beds is also a protection against large pressure buildup due to occlusion.…”
Section: Background In Cancer Cell Mechanicsmentioning
confidence: 99%
See 2 more Smart Citations